Comparison of the physical acoustic channel response of a line array of thin rectangular bars to an equivalent model of thin vibrating rectangular pistons. - Chambers, Shane; James, Ralph; Duncan, Alexander (Acoustical Society of Australia, 2012)
The resolution of an array is determined by the number and spatial distance of apertures (channels) within the array and the geometry of each aperture. The accurate design of acoustic sensing arrays relies on an a prioiri estimate of the expected far field radiation pattern of reciprocally behaved elements chosen for each aperture which is difficult to calculate under damped and loaded conditions. The estimated response of one channel of a vertical line array, when modeled as a series of rectangular vibrating pistons on a rigid baffle, is compared to the measured response of one channel of a line array comprised of a series of thin rectangular bars under load and operating off resonance. Although simple modeling can predict the 3dB main lobe width of the channel with some accuracy, loading and damping effects will alter the individual element response and hence the sensitivity of the array and side lobe magnitudes when off axis steering. This is important to note when estimating array gain and noise contributions from sidelobes under steered conditions.